2016
DOI: 10.4137/oed.s38863
|View full text |Cite
|
Sign up to set email alerts
|

Association of Anti-VEGF Injections with Progression of Geographic Atrophy

Abstract: Age-related macular degeneration (AMD) is one of the leading causes of blindness in developed countries in people over the age of 60 years. One of the forms of advanced AMD is wet AMD. Wet AMD is a result of leakage and bleeding from abnormal neovascularization. The principal treatment for wet AMD is intravitreal anti-VEGF injections. A second form of advanced AMD is geographic atrophy (GA). GA refers to large areas of retinal pigment epithelium loss. In the literature, there is some concern that anti-VEGF inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…No treatments are available for avAMD. The two major limitations of anti-VEGFs are the lack of improvement of vision in 60-70% of patients and adverse effects (Nesmith et al, 2014) including more rapid progression of GA (Enslow et al, 2016), increased intraocular pressure, retinal detachment, endophthalmitis, photoreceptor cell death and thinning of the inner neuronal layer of the retina (Saint-Geniez et al, 2008;Scott & Bressler, 2013). In addition to the adverse effects, the issues associated with logistics of blind or low-vision patients traveling to a clinic on a monthly basis result in a significant number of patients discontinuing treatment, which has been reported to be from 57% over five years (Boulanger-Scemama et al, 2015) to as high as 71% within 24 months (Lad et al, 2014).…”
Section: Amd Is a Major Cause Of Acquired Irreversible Blindness In Amentioning
confidence: 99%
“…No treatments are available for avAMD. The two major limitations of anti-VEGFs are the lack of improvement of vision in 60-70% of patients and adverse effects (Nesmith et al, 2014) including more rapid progression of GA (Enslow et al, 2016), increased intraocular pressure, retinal detachment, endophthalmitis, photoreceptor cell death and thinning of the inner neuronal layer of the retina (Saint-Geniez et al, 2008;Scott & Bressler, 2013). In addition to the adverse effects, the issues associated with logistics of blind or low-vision patients traveling to a clinic on a monthly basis result in a significant number of patients discontinuing treatment, which has been reported to be from 57% over five years (Boulanger-Scemama et al, 2015) to as high as 71% within 24 months (Lad et al, 2014).…”
Section: Amd Is a Major Cause Of Acquired Irreversible Blindness In Amentioning
confidence: 99%
“…Although the current treatment of AMD with intravitreal anti-VEGF injection offers new hope to thousands of patients with neovascular AMD, there are risks of adverse effects, including severe atrophy of choriocapillaris due to repeated treatment. [36][37][38] In contrast, targeting macrophages to blunt excessive VEGF upregulation can be a promising strategy in CNV therapy. A previous report showed that inhibition of M2type macrophage polarization by doxycycline as an alternative therapeutic approach against long-term anti-VEGF treatments, attenuated IL-1b-induced pathological blood vessel growth.…”
Section: Discussionmentioning
confidence: 99%
“…PBMC from the patients who had MA produced increased levels of VEGF. Previous studies have shown that enhanced MA progression in nAMD patients is associated with anti-VEGF injections [ 52 ]. In the present study, a numerically greater proportion of patients with MA had received more anti-VEGF injections than those without but this did not reach statistical significance ( P = 0.056).…”
Section: Discussionmentioning
confidence: 99%